Increased B cell-activating factor (BAFF) level in the sputum of children with asthma - Hye Mi Jee; Bong Seok Choi; Kyung Won Kim; Myung Hyun Sohn; Man Yong Han; Kyu-Earn Kim (Korean Pediatric Society, 2010)
PurposeB cell-activating factor (BAFF) is a tumor-necrosis factor (TNF) superfamily member best known for its role in the survival and maturation of B cells. BAFF activity is observed in naïve cells as well as in effector/memory T cells. We aimed to explore whether BAFF in sputum is expressed at elevated levels in asthmatic airways and associated with eosinophilic inflammation, pulmonary function, and bronchial hyperresponsiveness in children.MethodsOne hundred and fifty-four asthmatic children and 98 healthy children were enrolled in the study. Sputum supernatants were collected and sputum BAFF and eosinophil cationic protein (ECP) levels were measured. We performed pulmonary function tests and methacholine challenge tests, while measuring total eosinophil count, total serum IgE, and serum ECP in all subjects.ResultsAsthmatic children had significantly higher levels of BAFF in induced sputum [26.50 (10.50-100.27) pg/mL] compared to healthy children [18.32 (7.68-44.63) pg/mL; P=0.011]. Sputum BAFF positively correlated with sputum eosinophils (γ=0.406, P<0.001) and sputum ECP (γ=0.789, P<0.001). Significant negative correlations were found between sputum BAFF and FEV1 (γ=-0.291, P<0.001) or post-bronchodilator FEV1 (γ=-0.334, P<0.001), whereas nonsignificant correlations were found between sputum BAFF and bronchial hyperresponsiveness, serum eosinophil count, and serum ECP.ConclusionThese findings suggest that BAFF may play a role in childhood asthma, and BAFF levels in sputum could be a supportive marker that represents airway inflammation, especially eosinophilic inflammation.